The Importance of Bearing Witness in Edwin Cameron’s Witness to AIDS (2005) - Ortega Montero, Oscar (Archīum Ateneo, 2024)
Edwin Cameron’s memoir Witness to AIDS (2005) was the first HIV/AIDS memoir published in South Africa in the midst of the worst years of the epidemic. The narrative discloses essential facts about his experience living with the virus. In this paper, I argue that Edwin Cameron’s intellectually savvy and powerful testimony opened up a widespread national debate on citizen participation in policy-decision making and public accountability in South Africa. My analysis revolves on the interplay between whiteness, privilege, and access to life-saving drugs in the on-going construction of democratic and transparent post-Apartheid South Africa. Edwin Cameron’s position of privilege as former Constitutional Court judge and prominent human rights lawyer is used to benefit poverty-stricken South Africans, who are victims of the socioeconomic imbalances created by Apartheid over the years. Witness to AIDS also explores the obstacles to accessing medicines and the ethical choices involved in public health policies and creating of legal frameworks for social justice. Finally, the memoir sheds light on the devastating consequences of persisting inequalities and political inaction, and how breaking the silence, as well as the therapeutic benefits of life-writing, operate as stand-ins for national trauma.